(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Database re-appropriating is a common circulated registering perspective that empowers data owners to misuse its on-request accumulating and computational assets. The guideline challenge is keeping up the data arrangement concerning entrusted parties. We propose a combination of triple randomized algorithms namely 3DES, AES, Blowfish. The data owner can select between the encryption methods which is suitable. As each of the algorithms takes a different block size as input and also has various key sizes. Another issue that arises is the redundancy of data. When many copies of identical data are stored, the storage size decreases, and large storage space is required. Here data reduplication technique, which is used to identify duplicate files using the hash code value method for better storage space.